Mesenchymal stem cells for immune modulation in systemic lupus erythematosus: From bench research to clinical applications - Ginting, Andi R.; Munir, Delfitri; Amin, Mustafa M.; Darlan, Dewi M.; Putra, Agung; Rusda, Muhammad; Mutiara, Erna; Mayasari, Evita; Rozi, Muhammad F. (Narra J, 2024)
Systemic lupus erythematosus (SLE) is a prevalent autoimmune disease affecting multiple organ systems. Disease progression is inevitable as part of its natural course, necessitating aggressive therapeutic strategies, particularly with the use of immunosuppressants. Long-term use of steroids and other immunosuppressants is associated with significant adverse effects. Mesenchymal stem cells (MSCs) have been shown to modulate the immune response, leading to immunosuppressive effects against self-antigens. MSCs have demonstrated the ability to modulate several immune cell populations, contributing to favorable outcomes in controlling immune and inflammatory conditions. Recent evidence has shown an increase in Treg and Breg cell subsets following MSC administration, along with modulation of other immune cells, including dendritic cells, B cells, and T cells. However, the balance between MSC pro-inflammatory and anti-inflammatory phenotypic activation remains a critical factor in determining therapeutic outcomes. Various covariates also influence the efficacy of MSC therapy. The aim of this study was to provide a comprehensive overview of the utilization of mesenchymal stem cells (MSCs) in SLE treatment, leveraging their immunomodulatory and immunosuppressive capabilities. Understanding the fundamental preclinical effects of MSCs and recent findings from clinical studies may enhance the potential of MSC therapy in the management of SLE patients.